SEMIPRIME AND NILPOTENT FUZZY LIE ALGEBRAS - Nour Alhouda Alhayek; Samer Sukkary (Journal of New Theory)
– In this paper, we have introduced the concept of semiprime fuzzy Lie algebra and proved that every fuzzy Lie algebra of semiprime (nilpotent) Lie algebra is a semiprime (nilpotent)